Herbal oral care: an old concept or a new model? - Ahmed, Junaid; Shenoy, Nandita; Binnal, Almas; Mallya, Laxmish P.; Shenoy, Ashok (International Journal of Research in Medical Sciences, 2017)
Ayurveda, the oldest medical science originating from Indian subcontinent, has been practiced since the 12th century BC. Its objective is to accomplish physical, mental, social and spiritual well- being by adopting preventive, health promoting and holistic approach towards life. Ayurveda is the science that developed as humans evolved and has stood the test of time. Oral diseases are major health problems worldwide and are not limited to dental caries and periodontal diseases but to various autoimmune conditions. Oral health influences the general quality of life and poor oral health is linked to chronic conditions and systemic diseases. Recently there is renewed interest in use of various Ayurvedic drugs for oral and dental health.